Assesing Student Needs for E-Learning Medical Tutorial at The Faculty of Medicine Universitas Gunadarma - Rena Fuji Erin Setyawati; Rama Dian Syah; Sofian Zulenka; Bhakti Gunawan (Asosiasi Dosen Muda Indonesia, 2026)
Tutorials are widely employed in medical education as a form of problem-based learning, utilizing clinical cases to stimulate discussion. However, in practice, tutorial dynamics can influence the achievement of learning objectives. The integration of e-learning as a complementary media to face-to-face instruction offers a promising opportunity to optimize tutorial-based learning. This study aimed to assess medical students’ needs regarding the incorporation of e-learning in tutorial sessions. A mixed-methods approach was conducted, combining quantitative descriptive analysis with qualitative narrative inquiry. The study sample comprised 99 medical students from the Faculty of Medicine, Universitas Gunadarma (FKUG), who met the predefined inclusion and exclusion criteria. Quantitative data were collected through a tutorial evaluation questionnaire utilizing a Likert scale, while qualitative insights were gathered via focus group discussions (FGDs) to explore students’ specific e-learning requirements. Quantitative findings indicated that the tutorial learning process was rated as good to very good. Nevertheless, qualitative analysis revealed students’ desires for enhanced e-learning features, including chat rooms, feedback mechanisms, and video conferencing capabilities. These findings suggested that while current tutorial sessions function effectively, their efficacy could be further enhanced through the integration of e-learning applications. In conclusion, the development of e-learning tutorial platforms tailored to medical education is imperative to address students' evolving needs and to augment the tutorial learning experience.